A brief review of the cubic star on structural design, applications, and future perspective - Ma, Quanjin; Rejab, M. R. M.; Sun, Bo; Merzuk, M. N. M. (Penerbit Akademia Baru, 2021)
With the increasing diversification of space missions, the cube star, as a standard module-based miniature spacecraft, has gradually become increasing research interest and development in the field of aviation based on its low cost, high integration, and short development cycle. This paper reviews the design, application, and prospect of cube star, which analyzes the standardized structural design, attitude system, power system, communication measurement, and control design. It is focused on the application areas of cube star in demodulation of satellite signals, space exploration, and discovery technology verification, earth observation, communication interruption, etc. Finally, the development trend of future cube star technology is analyzed.